Slavic-root verbs in CP: loanwords and problematic cases - Smetonienė, Anželika (Lietuvių kalba, 2019)
Although being a comparatively small-volume source, the Catechism of Merkelis Petkevičius (CP) discloses the complexity of analysing Lithuanian loan verbs and Slavic-root hybrids. Conducting research on loanwords from the Slavic languages, the main focus is usually laid on nominal words. The key rule applied while analysing the verbs of Slavic origin is based on the compliance between the distinguished suffixes in the analysed words and the suffixes characteristic of the Slavic languages. However, Slavic-root loanwords are also found, the suffixes of which do not have any equivalents in the Slavic languages. Traditionally such verbs are assigned to hybrids but they may be of two types. The Slavic-root verbs were selected from CP, which contributed to revealing the problems encountered while analysing them. The majority of Slavic-root verbs in the CP are attributed to regular loanwords, which are also reflected in the adjacent text in Polish. Several words fall under the category of problematic Slavic-root verbs. The suggested division of hybrids into derivational and adaptational ones is determined by several principles. The hybrid, when a Slavic-root verb does not have precise suffix equivalents and due to the objective reasons cannot be seen as a loanword (there is no word in the Lithuanian language, which can serve as a derivational base word), is regarded to be an adaptational one, i.e., its morphological component that formally complies with the suffix, underwent changes in the process of integration but modifications in the meaning are rarely identified in such cases (liecavoti, -avoja, -vojo CP 217,23). Derivational hybrids are the verbs, which have a word of common root in the recipient language and the derivational link can be envisaged between them (prarakauti, -auja, -avo CP 160,17, pasnykauti, -auja, -avo CP 88,25). Such hybrids are more frequently based on the meanings of base word and this may lead to some differences in the meanings of respective root verbs in the Slavic languages.
Keywords: M. Petkevičius; catechism; verbs; loanwords; hybrids